Chemopreventative potential of Salsola tuberculatiformis Botch and Compound A in the differential regulation of IL-1Ra:IL-1α in UVB exposed skin keratinocytes - T. Magcwebeba; L. McEvoy; S. Hayward; T. Tait; J.L Quanson; L. Kelbe; WCA Gelderblom; M. Lilly; A.C Swart; P. Swart (Phytomedicine Plus)
Background: Salsola tuberculatiformis Botsch, commonly known as Gannabos, is a Namibian shrub known for its contraceptive properties in rats and its ability to modulate adrenal steroidogenesis both in vitro and in vivo. Due to the labile nature of the active compounds in the shrub, a more stable synthetic analogue, Compound A, was synthesized. This compound has demonstrated similar contraceptive and steroidogenic properties as the original extract from S. tuberculatiformis. Additionally, Compound A has shown potent anti-inflammatory and anti-cancer effects in skin, raising the question of whether the S. tuberculatiformis extract might exhibit similar properties. Purpose: The study aimed to evaluate the anti-inflammatory and anti-carcinogenic properties of S. tuberculatiformis extract and Compound A, particularly their effects on UVB-induced inflammation, cell growth parameters, and oxidative status in HaCaT cells. Methods: The biological activity of S. tuberculatiformis extract and Compound A was assessed using a cytochrome P450 assay. Anti/pro-inflammatory effects were evaluated by measuring IL-1α and IL-1Ra production using an ELISA assay. Additionally, the study monitored cell viability through ATP production, apoptosis via Caspase-3 activity, and oxidative stress using the DCFDA assay. Results: S. tuberculatiformis extract inhibited IL-1α production at lower concentrations while increasing IL-1Ra at higher concentrations. This was associated with reduced cell viability and increased pro-oxidant (ROS) and pro-inflammatory activity (intracellular IL-1α). Compound A, on the other hand, reduced IL-1Ra and IL-1α levels by inducing apoptosis. However, at higher concentrations, Compound A significantly increased extracellular IL-1Ra levels and enhanced pro-apoptotic and pro-oxidant activity. The extract exhibited different anti-inflammatory effects compared to Compound A, as evidenced by the increased intracellular IL-1Ra: IL-1α ratio. Conclusion: The data suggest that S. tuberculatiformis acts as an anti-inflammatory agent at low concentrations by inhibiting intracellular IL-1α production, while at higher concentrations, it regulates pro-inflammatory signaling through IL-1Ra. These anti/pro-inflammatory effects may have potential relevance in wound healing. Compound A displayed a novel indirect anti-inflammatory effect by removing inflamed and damaged cells via apoptosis and ROS production. The pro-oxidant activity of Compound A, potentially due to aziridine formation, appears to accelerate the progression of damaged cells into apoptosis.